Comparison of MRI and Histopathology with regard to Intramedullary Extent of Disease in Bone Sarcomas. (29th November 2019) - Gulia, Ashish; Puri, Ajay; Subi, T. S.; Gupta, Srinath M.; Juvekar, S. L.; Rekhi, Bharat
Abstract : In today's era, limb salvage surgery is the procedure of choice and current standard of care in appropriately selected patients of bone sarcomas. For adequate oncologic clearance, preoperative evaluation of the extent of tumor is mandatory. The present study was done to compare measurements of bone sarcomas (osteosarcoma, Ewing's sarcoma, and chondrosarcoma) as determined by magnetic resonance imaging (MRI) with the histopathological extent seen on resected specimens. We prospectively evaluated 100 consecutive patients with a diagnosis of bone sarcoma who underwent limb salvage surgery between May 2014 and December 2014. The maximum longitudinal (cranio-caudal) dimension of tumor on the noncontrast T1-WI sequence of MRI (irrespective of whether it was pre/postchemotherapy) was compared with the gross dimensions of the tumor on histopathology. The arithmetic mean difference, Wilcoxon signed-rank test, and Spearman's correlation analysis were used to test the differences and correlation between groups. Mean tumor size on MRI based on the largest extent on MRI was 12.1 ± 4.85 cm (mean ± standard deviation), while it was 10.77 ± 4.6 cm (mean ± standard deviation) on histopathology. In 79 cases, MRI overestimated the extent of disease; the mean was 1.79 cm with a standard deviation of 1.56 cm. When the disease extent was underestimated on MRI (13 cases), the mean was 0.58 cm with a standard deviation of 0.43 cm. In 8 cases (osteosarcoma (7), Ewing's sarcoma (1)), MRI measurement was equal to histopathology. The Spearman correlation analysis showed a high correlation of tumor length on histopathology with the MRI for all patients ( R = 0.948, P < 0.0001 ). We thus conclude that MRI is accurate in delineating the extent of bone sarcomas. A margin of 2 cm from the maximum tumor extent is adequate to ensure appropriate surgical resection.